Personal Hygiene and The Occurrence of Contact Dermatitis in Rice Farmers - Putri, Prestasianita; Tri Afandi, Alfid (Universitas Bondowoso, 2024)
ABSTRACT Background: Prevention of dermatitis is significant for the community, especially for farmers who have a high risk of developing this disease. The symptoms of dermatitis of farmers who work in the fields are affected by a decrease in his personal hygiene level. Personal hygiene is included in the occurrence of dermatitis in farmers who work in the areas. Method: This research is non-experimental quantitative research with an analytic survey design through a cross-sectional approach. The sampling technique used in this research is cluster sampling. Respondents are rice farmers who work directly in the fields, obtained as many as 110 respondents in five regions in East Java. Results: The respondents' criteria are that they have worked for at least one year, are farm laborers (working farmers), and are willing to be respondents. The results of the Chi-Square statistical test show that the value of p = 0.044 indicates a value of p <0.05. These results mean that there is a relationship between personal hygiene and the occurrence of contact dermatitis in farmers. Conclusion: The incidence of this dermatitis can cause a decrease in activity in farmers, so it can affect the mechanism of work patterns in farmers.